2023
DOI: 10.3390/cmd4030020
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities Associated with Alternative Fuels in Model Seawater-Compensated Fuel Ballast Tanks

Abstract: The biocorrosion of carbon steel poses a risk for ships combining seawater and fuel in metal ballast tanks. Ballast tanks were simulated by duplicate reactors containing carbon steel coupons and either petroleum F76 (petro-F76), Fischer–Tropsch F76 (FT-F76), or a 1:1 mix of both fuels, to investigate whether the alternative fuel FT-F76 influenced this risk. The polycarbonate reactors were inoculated with seawater, and the control reactors did not receive fuel. The reactors were monitored for 400 days, and they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…croflora. A low rate of oxygen diffusion across the polycarbonate housing the reactors was hypothesized as a reason for the limited sulfate reduction activity and the possible promotion of sulfide oxidation [39][40][41][42] consistent with the detection of a high relative abundance of sulfide-oxidizing bacteria in two of the reactors [18]. The relatively low levels of sulfate reduction and dissolved iron suggested that the rate of corrosion was relatively slow.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…croflora. A low rate of oxygen diffusion across the polycarbonate housing the reactors was hypothesized as a reason for the limited sulfate reduction activity and the possible promotion of sulfide oxidation [39][40][41][42] consistent with the detection of a high relative abundance of sulfide-oxidizing bacteria in two of the reactors [18]. The relatively low levels of sulfate reduction and dissolved iron suggested that the rate of corrosion was relatively slow.…”
Section: Introductionmentioning
confidence: 70%
“…Duplicate reactors containing 24 coupons (1018 carbon steel, Metal Samples, Munford, AL measuring 1.3 cm × 7.6 cm × 0.15 cm) were inoculated with approximately 2550 mL of seawater from San Diego Bay Harbor (San Diego, CA, USA) and a total of 120 mL of either petro-or Fischer-Tropsch F76 (FT-F76) fuel or a 50:50 mix of both fuels (Figure 1 and Table 1) and were incubated for 400 days. Note that approximately 6 × 10 −6 moles of oxygen were diffused into a reactor per day [49] based on the oxygen permeability properties of the polycarbonate used in the construction of the reactor [18]. untreated nonsterile sediments consisting of a slurry of 100 mL of seawater and a 100 g (wet weight) sediment.…”
Section: Reactor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Halarcobacter was among the microbial groups recently identified in fuel reactors containing PetroF76 and FT-F76, along with other putative hydrocarbon degraders such as Marinobacter (81). Candidatus Pseudothioglobus singularis, a newly described Gammaproteobacteria, is a group that has been intensively characterized as a representative culture from within the SUP05 clade for its utilization of organic carbon and methylated amines for energy acquisition in marine environments (82).…”
Section: Discussionmentioning
confidence: 99%
“…Candidatus Pseudothioglobus singularis, a newly described Gammaproteobacteria, is a group that has been intensively characterized as a representative culture from within the SUP05 clade for its utilization of organic carbon and methylated amines for energy acquisition in marine environments (82). Nevertheless, until now Halarcobacter and Pseudothioglobus have not been investigated for genes or biosurfactants related to hydrocarbon degradation (81). Genomic inspection revealed here that Halarcobacter anaerophilus and Candidatus Pseudothioglobus singularis possess alkG rubredoxin and meta-cleavage pathway genes that could potentially be responsible for aromatic compound metabolism, suggesting roles for these populations in crude oil bioremediation in cold Arctic waters.…”
Section: Discussionmentioning
confidence: 99%